The Effect of The Addition of Promoting Microbes (PROMI) In Making Media of Pleurotus ostreatus - Karmila; Ira Taskirawati; Baharuddin (Journal of Sylva Indonesiana, 2020)
In making oyster mushroom growing media, one of the stages that must pass is composting of growing media (baglog). At this stage, it takes a week or more to compile the media, so the media is ready to be inoculated by the fungus. This long composting time, economically slow down production in the cultivation of oyster mushrooms. Thus, using an activator to speed up the composting process is often done. During this time, the most widely used activators to shorten composting time is Effective Microorganism (EM4). In this study, another type of activator with the same function as EM4 was tried, namely Promoting Microbes (PROMI). The purpose of this study to determine the effect (dose) compromise on the making of oyster mushroom growing media to mycelium growth time, pinhead growth time; harvest time; the number of the fruiting body, and the weight of fresh mushrooms.Â  The raw material used candlenut wood sawdust (Aleurites moluccana Willd) in the making of media. The method used in this study is the making of growing media, composting, sterilization, inoculation of the fungus, and maintenance. Growing media consisted of sawn wood sawdust, PROMI, bran, CaSO4, CaCO3, and water. The treatment used is the addition of compromise to the growing media before composting. The doses of PROMI given are as follows: 0 g (P1); 0.25 g (P2); 0.5 g (P3), and 0.75 g (P4), each of which dissolved in 200 ml of water. This study's results indicate that different PROMI when mixing raw materials influences the time of mycelium closure in growing media and the time of harvesting mushroom fruit bodies. For the time of mycelial closing, giving as much as 0.5 g, PROMI has different control effects.Â  The provision of PROMI as much as 0.5 g and 0.75 g also influences the control in terms of harvest time.